2023
DOI: 10.1021/acs.est.3c08132
|View full text |Cite
|
Sign up to set email alerts
|

New Barrier Role of Iron Plaque: Producing Interfacial Hydroxyl Radicals to Degrade Rhizosphere Pollutants

Fan-Li Meng,
Xin Zhang,
Yi Hu
et al.

Abstract: Iron plaque, as a natural barrier between rice and soil, can reduce the accumulation of pollutants in rice by adsorption, contributing to the safe production of rice in contaminated soil. In this study, we unveiled a new role of iron plaque, i.e., producing hydroxyl radicals (•OH) by activating rootsecreted oxygen to degrade pollutants. The •OH was produced on the iron plaque surface and then diffused to the interfacial layer between the surface and the rhizosphere environment. The iron plaque activated oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…As shown in Figure b, the treatment with Fe 3+ and H 2 O 2 achieved a removal rate of 28.1% within 24 h, and the addition of cysteine further increased the value to 1.23 times. It is known that the Fenton reaction can be triggered by either Fe 3+ or Fe 2+ , which was the major iron species in previously reported iron plaque. , In our study, the Fe 2+ -mediated Fenton reaction had a significantly higher efficiency compared to the Fenton reaction triggered by Fe 3+ ( p = 0.002–0.044), indicating the superior performance of the cysteine-mediated ferrous iron plaque . Meanwhile, the kinetics of •OH were also monitored in the simulation experiment (Figure c).…”
Section: Resultsmentioning
confidence: 50%
See 2 more Smart Citations
“…As shown in Figure b, the treatment with Fe 3+ and H 2 O 2 achieved a removal rate of 28.1% within 24 h, and the addition of cysteine further increased the value to 1.23 times. It is known that the Fenton reaction can be triggered by either Fe 3+ or Fe 2+ , which was the major iron species in previously reported iron plaque. , In our study, the Fe 2+ -mediated Fenton reaction had a significantly higher efficiency compared to the Fenton reaction triggered by Fe 3+ ( p = 0.002–0.044), indicating the superior performance of the cysteine-mediated ferrous iron plaque . Meanwhile, the kinetics of •OH were also monitored in the simulation experiment (Figure c).…”
Section: Resultsmentioning
confidence: 50%
“…Iron plaque can act as both a barrier and a mediator for the degradation of rhizosphere pollutants. For example, the degradation of propane and atrazine was achieved at the interface of iron plaque . In this study, we found that the α-Fe 2 O 3 NM treatment and the cotreatment resulted in the highest PCB101 content in iron plaque; meanwhile, the removal rates of PCB101 in soil were similarly the highest in these two treatments.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…The intermediate byproducts comprised superoxide and hydrogen peroxide . The • OH was generated on the surface of iron plaque and subsequently diffused toward the interface layer between the iron plaque and the rhizosphere environment, facilitating the degradation of pollutants . Consequently, we employed a fluorescence probe to investigate the generation of • OH by iron plaque formed under various treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxyl radical (•OH) with the oxidation potential of 2.8 V is an important reactive oxygen species (ROS) that can efficiently degrade pollutants [48][49][50][51][52]. Efficient production of •OH is the key to achieving synchronous hydrogen production and water purification.…”
Section: Electrocatalytic Hydrogen Production Coupled With Pollutant ...mentioning
confidence: 99%